INTEGRATION BETWEEN SYSTEMS CADASTRE AND REGISTRY THROUGH A GEOGRAPHIC INFORMATION SYSTEM - Amorim, Amilton [UNESP]; Victorino, Priscila da Silva [UNESP]; Carmo, Alisson Fernando Coelho do [UNESP]; Juliao, Rui Pedro; DosSantos, J. G.; Fonte, C.; DeFigueiredo, R. F.; Cardoso, A.; Goncalves, G.; Almeida, J. P.; Baptista, S. (Univ Coimbra, 2015)
The advancement of computer technology, the development of Geographic Information Systems and the emergence of professionals qualified to work in this area, have shown to county and registry services new possibilities for information exchange between these two institutions. This fact allows a better description of the legal and geometric reality of the properties, and it also enables these data to be shared between other computing systems and made available to users in digital format. So, this work consist in investigate methods of integration between the Cadastre and Registration systems using Geographic Information Systems (GIS) developed for this purpose, through the technologies for interactive maps on the Internet. This method, still under development in this prototype, considers the need for these areas to acquire information contained in both systems, the improvement of administrative management in decision making. The first results indicate an improvement of customer service, streamlining the process in the solicitation of information related to real estate.
Keywords: Cadastral GIS; Multipurpose technical cadastre; Integration between systems cadastre and registry